Climate smart agriculture extension: gender disparities in agroforestry knowledge acquisition. (2nd January 2021) - Duffy, Colm; Toth, Greg; Cullinan, John; Murray, Una; Spillane, Charles
ABSTRACT: Numerous extension efforts promote climate smart agriculture (CSA) in Sub-Saharan Africa. The need to focus on gender disparity within CSA is widely understood. Given the prominence of female agriculturalists in Malawi, such focus can make a large impact on the country's rural sustainable development. This study quantifies the impact of extension techniques, including lead farmers, NGO trainers, and farmer clubs, on men and women farmers in Malawi by applying ordered logistic regression to data concerning post-extension increases in self-assessed CSA knowledge. Male and female farmers achieved increases in knowledge through traditional extension (NGO trainers and farmer clubs). However, these gains were less for female farmers. The interaction of female farmers with lead farmers (i.e. community members trained to train others) made increases in knowledge more likely. The impact of lead farmers was lessened by limited mobility and availability. Based on the study findings, we advocate for innovative approaches to CSA extension that aim to increase understanding of differing needs and preferences of female farmers. A failure to include women farmers in design from the outset misses a key opportunity to develop understanding of related societal challenges, increasing the likelihood of nominal participation and uneven outcomes among participating farmers.